INCREASED RISK OF SYNCHRONOUS COLORECTAL LESIONS IN PATIENTS REFERRED FOR ENDOSCOPIC MUCOSAL RESECTION OF LATERAL SPREADING TUMORS - Maria Constanza TORELLA; Belén DUARTE; Mariano VILLARROEL; Juan LASA; Ignacio ZUBIAURRE (Arquivos de Gastroenterologia)
ABSTRACT BACKGROUND: Endoscopic mucosal resection is one of the most frequent therapeutic alternatives for large colorectal lateral spreading tumors. There are few data on the prevalence of synchronous lesions on these patients. OBJECTIVE: To describe the prevalence of synchronous colorectal lesions in patients referred for endoscopic mucosal resection of lateral spreading tumors >20 mm. METHODS: We reviewed the endoscopic database of our Department and identified adult patients who were referred for the resection of a colorectal lateral spreading tumor >20 mm and had a diagnostic colonoscopy performed up to six months before. The proportion of patients with at least one synchronous lesion was estimated. The following features were compared between patients with and without synchronous lesions: age, gender, bowel preparation quality and cecal intubation on index colonoscopy and therapeutic colonoscopy, serrated adenoma as index lesion. RESULTS: From December 2016 to November 2017, we identified 70 patients who fulfilled inclusion criteria. Median size of lesions was 25 mm (20-45). Eighty percent were located in the right colon and 35.71% were serrated adenomas. Synchronous lesion rate was 38.57%. Bowel preparation quality was similar in both groups when comparing both index and therapeutic colonoscopies. Patients with synchronous lesions had a higher proportion of serrated adenoma as index lesion than patients without synchronous lesions [51.85% vs 25.58%, OR 3.13 (1.13-8.68), P=0.03]. CONCLUSION: We found a high prevalence of synchronous lesions among patients with a large colorectal lateral spreading tumor. This risk seems to be increased if index lesions are serrated adenomas.